A model of a specialist transitional support and liaison service within the Offender Personality Disorder Pathway in Wales: Learning from a regional pilot service. (September 2019) - O'Meara, Aisling; Morgan, Louise; Godden, Stephen; Davies, Jason
The process of transitioning from custody to the community can be a time of increased risk of reoffending and heightened anxiety brought on by uncertainty of future plans and unfamiliarity of new surroundings. This period can be particularly problematic for those experiencing complex needs or suffering with mental health difficulties. To address this concern, the Offender Personality Disorder Pathway (OPDP) in Wales established a Transitional Support Liaison service. This pilot service began with a focus on women's criminal justice journeys, and evident benefits led to service expansion to additionally address men's transitions to the community through Approved Premises. This practice note outlines the learning from these services, presenting a model of service delivery that can be adopted and expanded more widely. The paper concludes with recommendations and plans for service expansion.